2013
DOI: 10.1371/journal.pntd.0002476
|View full text |Cite
|
Sign up to set email alerts
|

How to Improve the Early Diagnosis of Trypanosoma cruzi Infection: Relationship between Validated Conventional Diagnosis and Quantitative DNA Amplification in Congenitally Infected Children

Abstract: BackgroundAccording to the Chagas congenital transmission guides, the diagnosis of infants, born to Trypanosoma cruzi infected mothers, relies on the detection of parasites by INP micromethod, and/or the persistence of T. cruzi specific antibody titers at 10–12 months of age.Methodology and Principal FindingsParasitemia levels were quantified by PCR in T. cruzi-infected children, grouped according to the results of one-year follow-up diagnosis: A) Neonates that were diagnosed in the first month after delivery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 24 publications
(38 reference statements)
1
77
0
2
Order By: Relevance
“…The most sensitive technique was qPCR, which has emerged as a promising diagnostic test, particularly for infections with parasite burdens below the detection limit of microscopy [25]. Nevertheless, multiple infant specimens were still needed to achieve optimal detection.…”
Section: Discussionmentioning
confidence: 99%
“…The most sensitive technique was qPCR, which has emerged as a promising diagnostic test, particularly for infections with parasite burdens below the detection limit of microscopy [25]. Nevertheless, multiple infant specimens were still needed to achieve optimal detection.…”
Section: Discussionmentioning
confidence: 99%
“…The DTU TcV has been reported in 80-100% of congenital cases in Argentina, Bolivia, Southern Brazil, Chile, and Paraguay (Virreira et al, 2006a(Virreira et al, , 2007Burgos et al, 2007;Corrales et al, 2009;Diez et al, 2010;Bisio et al, 2011;Ortiz et al, 2012;Bua et al, 2013;Garcia et al, 2014;Llewellyn et al, 2015). DTUs TcII and TcVI have been reported in neonates from Argentina, Bolivia, Brazil (Bahia state) and Chile (Virreira et al, 2006a;Burgos et al, 2007;Ortiz et al, 2012;Garcia et al, 2014), whereas TcIII has been identified in Paraguay (del Puerto et al, 2010) and TcI in some neonates from Argentina, Chile and Colombia (Pavia et al, 2009;Ortiz et al, 2012;Bua et al, 2013).…”
Section: Parasite Diversity and Human Congenital Chagas Diseasementioning
confidence: 99%
“…In the face of new negative findings in parasite detection, a third control visit is pursued around 10 mo after delivery for detection of parasitespecific Abs through serological assays, which will confirm the positive or negative diagnosis for T. cruzi infection. Nowadays, this is changing due to the development of new tools that allow the confirmation of T. cruzi infection (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Although the production of proinflammatory cytokines like IL-1b, IL-6, and TNF-a in response to T. cruzi Ags and the spontaneous release of TNF-a in uninfected infants born to T. cruzi-infected mothers (B 2 M + ) have been described, the levels of these cytokines in congenitally infected newborns are rather low (11,(13)(14)(15)(16), suggesting that the immune response might be an important factor in vertical transmission (17). By using a quantitative PCR (qPCR), we have previously demonstrated that the parasitemia of congenitally infected infants is highly variable at birth (7,18), and this fact posed the question whether T. cruzi-infected children also exhibit variable levels of chemokines and cytokines that might correlate with parasite burden and predict congenital infection. In this context, our study aimed to evaluate the chemokine and cytokine profiles in groups of congenitally infected and uninfected infants born to T. cruzi- Received for publication December 1, 2015.…”
mentioning
confidence: 99%